Quails in Mexico: Needs and Opportunities - John P. Carroll; Jack Clinton Eitniear (National Quail Symposium Proceedings, 2017)
Recently, McGowan et al. (1995) completed a worldwide conservation strategy for all species of partridges, quails, and francolins. They identified priority species and projects for the next 5 years. Mexico was identified as a critical country in Latin America because of the presence of a large number of species of quails (15) and presence of several species and one subspecies which received conservation status; the bearded tree-partridge (Dendrortyx barbatus), ocellated quail (Cyronyx ocellatus) and masked bobwhite (Colinus virginianus ridgwayi). We are presently undertaking research and conservation efforts on the critically endangered bearded treepartridge and use this to highlight concerns and opportunities related to quails in Mexico. This program includes local educational programs advertising the plight of this species, development of survey techniques, collection of life history data, and a complete survey of distribution of the species. From our efforts so far, we have found that local involvement and interest in rural communities is possible. We are finding that techniques, such as play-back of tape recorded calls, show great potential for both census and surveys of the bearded tree-partridge. Finally, we are finding that lack of basic life history and population data of these species can result in misguided development of conservation strategies